Non-random distribution of biocrust in a natural arid environment in the northern mexican plateau - Gutiérrez, M.; Pando Moreno, Marisela; Jurado, Enrique; González Rodríguez, Humberto; Marmolejo Monsiváis, José Guadalupe; Mendoza, D. (University of Budapest, 2018)
Abstract. Biocrust, as photosynthetic organisms, has been considered to show an inversely proportional relationship with vascular plant cover. However, some studies report association and facilitation relationships between them. This research explores whether i) biocrust is associated with shrub species, ii) biocrust cover is higher in undershrub microenvironments than in open areas between plants and, iii) soil moisture and solar radiation affect biocrust distribution. Biocrust cover was analyzed by morphotype in microenvironments under the canopy of two dominant shrub species (Larrea tridentata and Parthenium incanum) and in open areas. Soil moisture and solar radiation were recorded at each microenvironment. Thirty-three interception lines (975 points) were used to analyze the association between vascular plants and biocrust and 20 sampling plots to estimate morphotype cover. Results reveal a positive association between biocrust and plant species compared to open areas. Lichens and cyanobacteria showed a higher cover under L. tridentata than under P. incanum and in open areas, suggesting a species-specific facilitative association with L. tridentata, maybe due to a higher soil water content in this microenvironment. Mosses had lower cover in the open area where the highest solar radiation was recorded. Lichens and cyanobacteria distribution appeared to be related to soil moisture. Keywords: creosote bush, cyanobacteria, lichens, mosses, northeastern Mexico